An efficient procedure for concrete fracture analysis based on mesh refinement ergodicity - Chacón, G.; Rivarola, F. L.; van Huyssteen, Daniel; Steinmann, Paul; Etse, G. (Computational Mechanics, 2024)
In this paper a new procedure for modeling brittle fracture processes in concrete components is proposed in the framework of the so-called discrete crack approach and exploiting ergodic behaviour with respect to the refinement of the mesh. The complexity in controlling localized crack development in quasi-brittle materials like concrete usually necessitates very fine meshes that are associated with a very high computational cost. In this work, a method is proposed that exploits the ergodic behavior with respect to mesh refinement/density observed in simulations performed on randomly generated meshes. The proposed method is framed in the discrete crack concept, which avoids or minimizes mesh dependence. It considers the interaction between elastic solids or aggregates and nonlinear interfaces, where the fractures are described based on the relative displacements at the joints where energy dissipation occurs. To allow significant geometric flexibility in the modeling of elastic aggregates, Voronoi discretizations of virtual elements are used in combination with nonlinear interface elements. Numerical simulations of benchmark problems demonstrate that the proposed procedure accurately predicts failure behavior in brittle materials. Specifically, the peak load, crack path, and load–displacement relationship obtained from the averaged behavior of coarse-mesh simulations closely match those from very fine-mesh simulations. The results demonstrate that by taking advantage of both the well-known mesh flexibility of virtual element method and the observed ergodic behavior with respect to mesh density, the proposed procedure represents an efficient and accurate tool for modeling failure behavior in quasi-brittle materials such as concrete.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Interface element; Mesh refinement ergodicity; Virtual element method